Darwin's camera : art and photography in the theory of evolution - Prodger, Phillip (Oxford University Press, 2009)
Darwin's Camera tells the extraordinary story of how Charles Darwin changed the way pictures are seen and made. In his illustrated masterpiece, Expression of the Emotions in Man and Animals (1871), Darwin introduced the idea of using photographs to illustrate a scientific theory--his was the first photographically illustrated science book ever published. Using photographs to depict fleeting expressions of emotion--laughter, crying, anger, and so on--as they flit across a person's face, he managed to produce dramatic images at a time when photography was famously slow and awkward. The book desc.